Gender-based violence against women during the COVID-19 pandemic: recommendations for future - Abbas Ostadtaghizadeh; Mozhdeh Zarei; Nadia Saniee; Mohammad Aziz Rasouli (BMC, 2023)
Abstract Background Gender-based violence (GBV) includes any physical, sexual, psychological, economic harms, and any suffering of women in the form of limiting their freedom in personal or social life. As a global crisis, COVID-19 has exposed women to more violence, which requires serious actions. This work aims to review the most critical dimensions of the GBV against women, effective factors on it, and strategies for combating it during the COVID-19 pandemic in order to provide recommendations for future pandemics. Methods This study was conducted based on PRISMA-ScR. First, PubMed, Embase, Scopus, Web of Science, ProQuest, and Google Scholar were searched in April 2021 with no time limitation and location using the related keywords to COVID-19 and GBV. The searched keywords were COVID-19, gender-based violence, domestic violence, sexual violence, women, violence, abuse, and their synonyms in MESH and EMTREE. Duplicates were removed, titles and abstracts were screened, and then the characteristics and main results of included studies were recorded in the data collection form in terms of thematic content analysis. Results A total of 6255 records were identified, of which 3433 were duplicates. Based on inclusion criteria 2822 titles and abstracts were screened. Finally, 14 studies were eligible for inclusion in this study. Most of these studies were conducted in the United States, the Netherlands, and Iran, mostly with interventional and qualitative methods. Conclusions Strengthening ICT infrastructure, providing comprehensive government policies and planning, government economic support, social support by national and international organizations should be considered by countries worldwide. It is suggested that countries provide sufficient ICT infrastructure, comprehensive policies and planning, economic support, social support by collaboration between national and international organizations, and healthcare supporting to manage incidence of GBV against women in future pandemics.